Intended and unintended changes in length of stay following reconfiguration of emergency care departments. (15th January 2021) - Bogh, Søren Bie; Fløjstrup, Marianne; Möller, Sören; Bech, Mickael; Johnsen, Søren Paaske; Henriksen, Daniel Pilsgaard; Mogensen, Christian Backer; Lassen, Annmarie Touborg; Brabrand, Mikkel
Abstract: Background: The Danish health-care system has witnessed noticeable changes in the acute hospital care organization. The reconfiguration includes closing hospitals, centralizing acute care functions and investing in new buildings and equipment. Objective: To examine the impact on the length of stay (LOS) and the proportion of overnight stays for hospitalized acute care patients. Methods: This nationwide interrupted time series examined trend changes in LOS and overnight stay. Admissions were stratified based on admission time (weekdays/weekends and time of day), age and the level of co-morbidity Results: In 2007–2016, the global average LOS declined 2.9% per year (adjusted time ratio [CI (confidence interval) 95%] 0.971 [0.970–0.971]). The reconfiguration was overall not associated with change in trend of LOS (time ratio [CI 95%] 1.001 [1.000–1.002]). When admissions were stratified for either weekdays or weekends, the reconfiguration was associated with reduction of the underlying downward trend for weekdays (time ratio [CI 95%] 1.004 [1.003–1.005]) and increased downward trend for weekend admissions (time ratio [CI 95%] 0.996 [0.094–0.098]). Admissions at night were associated with a 0.7% trend change in LOS (time ratio [CI 95%] 0.993 [0.991–0.996]). The reconfiguration was not associated with trend changes for overnight stays. Conclusion: The nationwide reconfiguration of acute hospital care was overall not associated with change in trend for the registered LOS and no change in trend for overnight stays. However, the results varied according to hospitalization time, where admissions during weekends and nights after the reconfiguration were associated with shortened LOS.